Spain in our hearts : Americans in the Spanish Civil War, 1936-1939 - Hochschild, Adam (Houghton Mifflin Harcourt, 2016)
A sweeping history of the Spanish Civil War, told through nine American and British characters including Hemingway and George Orwell. It was a war between fascism, communism, and democracy that preceded World War II, and a tale of idealism and a noble cause that failed.